Implementation guidelines for a temporal intelligent system supporting organizational creativity - Mach-Król, Maria (Business Informatics, 2015)
The main aim of the paper is to present and discuss the implementation guidelines of a temporal intelligent system, intended to support organizational creativity. The discussion is based on the author’s proposal concerning such guidelines, on literature research, and on the author’s research concerning temporal intelligent systems. Thus, motivation for implementing a temporal intelligent system is presented, temporal aspects of organizational creativity are pointed out, related work on implementation methodologies is included, and finally a proposal of implementation guidelines is presented and discussed in detail
Informatyka Ekonomiczna = Business Informatics, 2015, Nr 4 (38), s. 45-54
Keywords: organizational creativity; temporal intelligent system; implementation guidelines; KADS; CAKE; twórczość organizacyjna; temporalny system inteligentny; metodyka wdrażania